Teaching of collective health in the ABC Medical School: some notes on the challenges of collective health in medical training - Carneiro Junior, Nivaldo (ABCS Health Sciences, 2015)
Introduction: Collective health, a field of knowledge and practices concerning health, illness and care, introduces medicine students to methodological and theoretical issues and intervention technologies for professional practice. Historically, collective health occupies a subordinate position within the political and pedagogical project which orients health education. This project is hospital‑centered and emphasizes biological themes. According to the Brazilian’s 1988 Constitution, health is a social right and the Health System is public and universal. New educational and health policies were then formulated. It is the role of Unified Health System to organize the training of human resources. The National Curriculum Guidelines for health undergraduate courses point to professional profiles which can meet population’s health needs. This requires new teaching methodologies and scenarios for pedagogical practices. From this view, the collective health teaching becomes very important. Experience report: Collective health in the Medical course at ABC Medical School was one of the basic disciplines for second year students. A new curriculum changed this. Until 2013, it was an annual discipline in three modules: epidemiology, biostatistics and policies and organization of health services. During the first year, themes of social and human sciences were approached as part of Professional Practices Basis. But the teaching of collective health faces several challenges: the great concentration, during this period, of Morphology and Physiology subjects, few contacts with health services and problems concerning illness and care. Conclusion: To solve this, new pedagogical strategies were developed, providing cognitive experiences and skills suitable to learning collective health subject matters. Positive results showed in recent Regional Medical Council examination supports these pedagogical strategies.